Adopting inflation targeting : practical issues for emerging market countries - Schaechter, Andrea...[et al] (IMF WashingtonUS, 2000)
Summarizes the lessons that can be drawn for emerging market countries on the operational and institutional policy challenges posed by inflation targeting.